Statistical data mining using SAS applications - Fernandez, George (Boca Raton: CRC Press, 2010)
Statistical Data Mining Using SAS Applications, Second Edition describes statistical data mining concepts and demonstrates the features of user-friendly data mining SAS tools. Integrating the statistical and graphical analysis tools available in SAS systems, the book provides complete statistical data mining solutions without writing SAS program codes or using the point-and-click approach. Each chapter emphasizes step-by-step instructions for using SAS macros and interpreting the results. Compiled data mining SAS macro files are available for download on the author$1 (Bs website. By following the step-by-step instructions and downloading the SAS macros, analysts can perform complete data mining analysis fast and effectively.s
Data Mining: A Gentle Introduction -- Preparing Data for Data Mining -- Exploratory Data Analysis -- Unsupervised Learning Methods -- Supervised Learning Methods: Prediction -- Supervised Learning Methods: Classification -- Advanced Analytics and Order SAS Data Mining Resources
Includes bibliography and index
Keywords: Statistics -- Data Mining; Statistics -- SAS Applications